2014
DOI: 10.1152/ajpendo.00345.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis in lethal canine Staphylococcus aureus pneumonia

Abstract: The clinical significance and even existence of critical illness-related corticosteroid insufficiency is controversial. Here, hypothalamic-pituitary-adrenal (HPA) function was characterized in severe canine Staphylococcus aureus pneumonia. Animals received antibiotics and titrated life-supportive measures. Treatment with dexamethasone, a glucocorticoid, but not desoxycorticosterone, a mineralocorticoid, improves outcome in this model. Total and free cortisol, adrenocorticotropic hormone (ACTH). and aldosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…Ample experimental and clinical evidence [29][30][31][32][33][34][35][36] shows that premature discontinuation of glucocorticoids in patients with severe sepsis or ARDS frequently (25-40%) leads to rebound systemic inflammation and clinical relapse (hemodynamic deterioration, recrudescence of ARDS, or worsening multiple organ dysfunction). Experimental animal sepsis models have demonstrated an early marked increase in ACTH levels that returns to baseline values at around 72 h [63]. Compared with healthy volunteers, clinical studies have found ACTH levels to be significantly lower in critically ill septic patients [14,64,65].…”
Section: Altered Crh/acth Synthesismentioning
confidence: 99%
“…Ample experimental and clinical evidence [29][30][31][32][33][34][35][36] shows that premature discontinuation of glucocorticoids in patients with severe sepsis or ARDS frequently (25-40%) leads to rebound systemic inflammation and clinical relapse (hemodynamic deterioration, recrudescence of ARDS, or worsening multiple organ dysfunction). Experimental animal sepsis models have demonstrated an early marked increase in ACTH levels that returns to baseline values at around 72 h [63]. Compared with healthy volunteers, clinical studies have found ACTH levels to be significantly lower in critically ill septic patients [14,64,65].…”
Section: Altered Crh/acth Synthesismentioning
confidence: 99%
“…High basal cortisol values in cats with cholestatic disease are a risk factor associated with poor short-term survival. Although increases in basal and ACTH-stimulated cortisol values are necessary for an animal's response to the stress of illness, studies in chronically ill humans 34 and septic dogs 8 show that sustained HPA hyperactivity eventually becomes detrimental and is correlated with decreased survival. Whether the same is true in cats is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Ample experimental and clinical evidence (29)(30)(31)(32)(33)(34)(35)(36) shows that premature discontinuation of glucocorticoids in patients with severe sepsis or ARDS frequently (25%−40%) leads to rebound systemic inflammation and clinical relapse (hemodynamic deterioration, recrudescence of ARDS, or worsening multiple organ dysfunction). Experimental animal sepsis models have demonstrated an early marked increase in ACTH levels that returns to baseline values at around 72 hours (63). Compared with healthy volunteers, clinical studies have found ACTH levels to be significantly lower in critically ill septic patients (14,64,65).…”
Section: Impairment Of Adrenal Cortisol Synthesismentioning
confidence: 99%